Corruption as a Social Phenomenon: Problems and Prospects for Combating Corruption - AKHMETOV, Arman Serikovich; ZHAMULDINOV, Victor Nikolaevich; KOMAROV, Oleg Evgenievich (Journal of Advanced Research in Law and Economics; Vol 9 No 5 (2018): JARLE Volume IX Issue 5(35) Fall 2018, 2018)
The purpose of this article is to present a comprehensive study and analysis of existing scientific approaches to the study of corruption as a social phenomenon, as well as to develop certain recommendations for preventing and combating corruption manifestations. The methodological basis of this work is formed by both general scientific and special legal methods of cognition. The presented scientific approaches to the study of corruption as a social phenomenon made it possible to develop an author’s justified position based on the existing achievements of the research community in the nature and essence of corruption. Based on domestic and foreign sources, the research allowed us to analyze the main issues of studying corruption as a social phenomenon, to identify a number of factors that are prerequisites for the emergence and development of corruption manifestations in society, as well as to develop a number of measures, which will help to combat corruption. The process of eradicating corruption is possible only through the joint work of the state, society, various civil society institutions and, ultimately, every citizen, who is responsible for his/her own actions and takes an active part in the anti-corruption policy of the state.